The relationship between family power and board communication quality in Turkish public family firms - ATILGAN, ÖZGÜR (My University, 2020)
The role of boards gained significant importance after the presentation of OECD guidelines that made the boards as an indispensible corporate goevrnance mechanism for effective communication between owners and shareholders, strategic guidence for the company, supervision of top level management and accountability for the shareholders and other external stakeholders. In family businesses, boards are considered as one of the most important governance mechanisms in establishing an effective communication channel between shareholders and top management and also within the family. Yet, it is not easy to measure the board communication quality. This study attempts to investigate the effects of family members proportion in boards and ownership concentration on communication quality by using board meeting attendance rate as a proxy measure for communication quality. For this purpose, secondary data from the annual reports, corporate governance compliance reports and general information on capital and shareholders of 162 family firms enlisted in Istanbul Stock Exchange (BİST) was obtained and the correlation analysis was performed. The results implicate that there is no significant relationship between family members proportion in boards and board attendance and also no significant relationship has been found between ownership concentration and board attendance. Results only indicate that higher family ownership concentration increases the family members proportion in boards.
Keywords: Family Boards; Family Ownership; Percentage of Family Members on Board; Board Meeting Attendance Rate; Communication Quality; Aile Kurulları; Aile Sahipliği; Gemideki Aile Üyelerinin Yüzdesi; Kurul Toplantılarına Katılım Oranı; İletişim Kalitesi